Lithuania : Insolvency and Creditor Rights Systems - World Bank (Washington, DC, 2013)
The legal environment in Lithuania to support creditor rights and debt enforcement is reasonably effective, and collateral regimes have been largely centralized and modernized. Consistent with a modern system, security interests may be granted in immoveable and moveable assets, including equipment, inventory, goods, receivables, and future property. In practice, security tends to be restricted to more reliable and liquid assets, such as immovables or fixed assets. Markets for moveable assets remain poorly developed or illiquid. Appeals remain a source of delay, and other procedures could be improved. The insolvency process in Lithuania has been almost exclusively one of liquidation, plagued by delay and procedural obstacles. A new insolvency law was adopted in July 2001, bringing to three the number of insolvency laws currently in effect. At the same time, a new Enterprise Restructuring Law became effective. As of November 2001, only a few cases had been filed under the new law, which a growing consensus of stakeholders consider to be unworkable and unfavorable to creditors. The process may be aided by the developing training guides and programs. Regulation of insolvency remains fragmented and weak, but shows evidence of an evolving structure. Court efficiency is stifled by a lack of specialization among judges, who are overloaded and poorly equipped to deal with bankruptcy cases, especially rehabilitations. The administrators' profession is marked by low standards, over-licensing, inadequate training and skills, and inconsistent performance. While much remains to be done, the national association of bankruptcy administrators is working to improve licensing standards and to strengthen continuing education and training for its members.